1991
DOI: 10.1001/archderm.1991.01680050100012
|View full text |Cite
|
Sign up to set email alerts
|

Localized vs Generalized Pyogenic Granuloma

Abstract: We herein report the unusual case of a previously healthy young man who had spontaneous development of multiple lobular capillary hemangiomata disseminated over the integument. Based on the observation that the single lesions exhibited (immuno)pathologic and ultrastructural features similar, if not identical, to those of late-stage pyogenic granulomas, we propose to nosologically include our patient's eruption within the disease spectrum of pyogenic granuloma. As opposed to the occurrence of localized forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The pathogenesis of this phenomenon is unclear. One author suggested that exogenous factors such as trauma and endogenous substances released from tumor cells may promote the development of these granulomas (Strohal et al , 1991). We describe a case of a intra‐oral pyogenic granuloma with recurrent nodules in the site of previously treated healing wound and adjacent gingival tissue resembling satellitosis on the skin.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of this phenomenon is unclear. One author suggested that exogenous factors such as trauma and endogenous substances released from tumor cells may promote the development of these granulomas (Strohal et al , 1991). We describe a case of a intra‐oral pyogenic granuloma with recurrent nodules in the site of previously treated healing wound and adjacent gingival tissue resembling satellitosis on the skin.…”
Section: Introductionmentioning
confidence: 99%
“…On review of the literature, only nine cases 10–17 of disseminated lobular capillary haemangioma have been reported (Table 2). These cases were characterized by the sudden development of numerous widespread lobular capillary haemangiomas ranging in size from 1 to 10 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to microscopic arteriovenous anastomoses, Strohal et al. 9 have suggested that an underlying inflammatory or neoplastic disease could trigger the development of multiple LCH's with release of angiogenic factors. Shimizu et al.…”
mentioning
confidence: 99%